Desain Sambungan Becak Tempel Berbasiskan Metode Quality Function Deployment (QFD) Dengan Pendekatan Design For Manufacturing and Asembly (DFMA) - Ridwansyah, Arrijal; Yohanes, Yohanes; Satriardi, Satriardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Transport for humans at the present time this is a very necessary thing. The modifications made by the people is by making two-wheeled vehicles or motorcycles into three or more wheeled vehicles for the transport of goods. Quality Function Deployment (QFD) is a method that serves to design tools according to the needs of the community, so we get the design parameters in the manufacture outboard rickshaw connection. Design For Manufacturing and Assembly (DFMA) is a method that serves to determine the most efficient manner in the product creation process and minimize the time of the assembly, while the time required in the assembly process outboard rickshaw is 545.75 seconds with time efficiency of 7.69%.Keyword: Conection, Pedicab, QFD, DFMA